New materials of the white rhinoceros Ceratotherium simum and auerochs Bos primigenius from a Late Pleistocene terrace of the Oued el Haï (NE Morocco) - two elements of the Maghrebi Palearctic fauna. (3rd October 2022) - Aouraghe, Hassan; van der Made, Jan; Haddoumi, Hamid; Agustí, Jordi; Benito-Calvo, Alfonso; Rodríguez-Hidalgo, Antonio; Lazagabaster, Ignacio A.; Souhir, Mohamed; Mhamdi, Hicham; El Atmani, Abderrahman; Ewague, Abdelhadi; Sala-Ramos, Robert; et al.
ABSTRACT: Most biogeographers considered the Maghreb to be part of the Palearctic biogeographic region, though it is relatively recently that the proportion of Palearctic species increased there. How and when exactly these biogeographic changes occurred is not well understood, but they are probably the result of the increasing aridification of the Sahara and decreasing global temperatures. Fossils of Bos primigenius and Ceratotherium simum from a new fossil locality in a terrace of the Oued el Haï (NE Morocco) contribute to our understanding of some of these biogeographic processes and their timing. They also suggest an age between ~57 and ~100 ka for the terrace. The same evolutionary change in Bos in Europe and the Maghreb suggests geneflow as the most parsimonious explanation, though parallel evolution is an alternative possibility. Oued el Haï has the oldest well-documented record of C. simum in the Maghreb. The dispersal of this species to North Africa, where it replaced C. mauritanicum, may have occurred during a 'Green Sahara Period' between 80–85 or 100–105 ka, when the Maghreb had acquired already a Palearctic character. The study of the biogeography and requirements of the large mammals of the Maghreb may provide information to calibrate the region's climate modelling.